Hyperkalemia in CKD: an overview of available therapeutic strategies - Costa, Davide; Patella, Gemma; Provenzano, Michele; Ielapi, Nicola; Faga, Teresa; Zicarelli, Mariateresa; Arturi, Franco; Coppolino, Giuseppe; Bolignano, Davide; De Sarro, Giovambattista; Bracale, Umberto Marcello; De Nicola, Luca; et al. (Frontiers in Medicine, 2023)
Hyperkalemia (HK) is a life-threatening condition that often occurs in patients with chronic kidney disease (CKD). High serum potassium (sKsK) is responsible for a higher risk of end-stage renal disease, arrhythmias and mortality. This risk increases in patients that discontinue cardio-nephroprotective renin–angiotensin–aldosterone system inhibitor (RAASi) therapy after developing HK. Hence, the management of HK deserves the attention of the clinician in order to optimize the therapeutic strategies of chronic treatment of HK in the CKD patient. The adoption in clinical practice of the new hypokalaemic agents patiromer and sodium zirconium cyclosilicate (SZC) for the prevention and chronic treatment of HK could allow patients, suffering from heart failure and chronic renal failure, to continue to benefit from RAASi therapy. We have updated a narrative review of the clear variables, correct definition, epidemiology, pathogenesis, etiology and classifications for HK among non-dialysis CKD (ND CKD) patients. Furthermore, by describing the prognostic impact on mortality and on the progression of renal damage, we want to outline the strategies currently available for the control of potassium (K+) plasma levels.